Endothelial damage and dysfunction in acute graft-versus-host disease - Cordes, Steffen; Mokhtari, Zeinab; Bartosova, Maria; Mertlitz, Sarah; Riesner, Katarina; Shi, Yu; Mengwasser, Joerg; Kalupa, Martina; McGeary, Aleixandria; Schleifenbaum, Johanna; Schrezenmeier, Jens Florian; Bullinger, Lars; et al. (Haematologica, 2021)
Clinical studies have suggested a potential involvement of endothelial dysfunction and damage in the development and severity of acute graft -versus -host disease (aGvHD). Accordingly, we found an increased percentage of apoptotic caspase 3 positive blood vessels in duodenal and colonic mucosa biopsies of patients with severe aGvHD. In murine experimental aGvHD, we detected severe microstructural endothelial damage and reduced endothelial pericyte coverage accompanied by reduced expression of endothelial tight junction proteins leading to increased endothelial leakage in aGvHD target organs. During intestinal aGvHD, colonic vasculature structurally changed, reflected by increased vessel branching and vessel diameter. As recent data demonstrated an association of endothelium-related factors and steroid refractory aGvHD (SR-aGvHD), we analyzed human biopsies and murine tissues from SR-aGvHD. We found extensive tissue damage but low levels of alloreactive T-cell infiltration in target organs, providing the rationale for T-cell independent SR-aGvHD treatment strategies. Consequently, we tested the endothelium-protective PDE5 inhibitor sildenafil, which reduced apoptosis and improved metabolic activity of endothelial cells in vitro. Accordingly, sildenafil treatment improved survival and reduced target organ damage during experimental SR-aGvHD. Our results demonstrate extensive damage, structural changes, and dysfunction of the vasculature during aGvHD. Therapeutic intervention by endothelium-protecting agents is an attractive approach for SR-aGvHD complementing current anti-inflammatory treatment options.